2019
DOI: 10.1038/s41398-019-0527-1
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine induces differential circular RNA expression in striatum

Abstract: Circular RNA (circRNA), a novel type of endogenous non-coding RNA, plays natural miRNA sponge effect that represses the activities of corresponding miRNAs through binding with them, thus modulating transcriptional expression of genes. Recent studies indicate that circRNAs are significantly enriched in the brain and some of them are derived from synaptic protein-coding genes. In addition, miRNAs are involved in synaptic plasticity, memory formation, and cocaine addiction. However, the role of circRNAs in cocain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…The existing literature on drug-induced circRNA expression has reported circRNA regulation in primary cortical neurons and the cerebellum in response to methamphetamine treatment, and in the striatum in response to cocaine self-administration [54][55][56]. None of the five heroin-associated circRNAs validated in the present study were regulated by psychostimulants in the aforementioned studies.…”
Section: Discussionsupporting
confidence: 41%
“…The existing literature on drug-induced circRNA expression has reported circRNA regulation in primary cortical neurons and the cerebellum in response to methamphetamine treatment, and in the striatum in response to cocaine self-administration [54][55][56]. None of the five heroin-associated circRNAs validated in the present study were regulated by psychostimulants in the aforementioned studies.…”
Section: Discussionsupporting
confidence: 41%
“…The use of advanced annotation tools and deep sequencing of ribosomal RNA (rRNA)-depleted and RNase R-digested RNA samples has revealed the existence of tens of thousands of circRNAs ( Hansen et al, 2013 ; Memczak et al, 2013 ; Guo et al, 2014 ; Rybak-Wolf et al, 2014 ; You et al, 2015 ). Interestingly, circRNA expression has been shown to be altered in various psychiatric disorders ( Zimmerman et al, 2020 ), autism ( Chen et al, 2020 ), cocaine addiction ( Bu et al, 2019 ), and Alzheimer’s disease ( Dube et al, 2019 ). Among the potential functions of circRNAs are interactions with RBPs, sequestration of miRNAs, and transcriptional control of gene expression ( Hentze and Preiss, 2013 ; Barrett and Salzman, 2016 ; Gokool et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Circular RNAs are endogenous non-coding RNAs with widespread distribution and various cellular function ( Hansen et al, 2013 ; Vicens and Westhof, 2014 ; Rybak-Wolf et al, 2015 ; Du et al, 2017 ; Greene et al, 2017 ; Li et al, 2018 ; Mehta et al, 2020 ). Numerous studies have shown that circRNAs have an important influence on many complicated neuropsychiatric disorders ( Cui et al, 2016 ; Zhang et al, 2018 ; An et al, 2019 ; Liu et al, 2019 ; Mahmoudi et al, 2019 ; Huang et al, 2020 ; Zhang Y. et al, 2020 ; Zimmerman et al, 2020 ), including drug addiction ( Huang et al, 2017 ; Bu et al, 2019 ; Li et al, 2019 , 2020 ; Zhang H. et al, 2020 ). Knockdown of circHomer1 ameliorates methamphetamine-induced neuronal injury through inhibiting Bbc3 expression ( Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%